Billy Summers : a novel - King, Stephen, 1947- (New York : Scribner, 2021)
Billy Summers is a man in a room with a gun. He$1 (Bs a killer for hire and the best in the business. But he$1 (Bll do the job only if the target is a truly bad guy. And now Billy wants out. But first there is one last hit. Billy is among the best snipers in the world, a decorated Iraq war vet, a Houdini when it comes to vanishing after the job is done. So what could possibly go wrong? How about everything.s
Keywords: Assassins -- Fiction; Undercover operations -- Fiction; Good and evil -- Fiction; Justice -- Fiction; Veterans -- Fiction; Revenge -- Fiction; City and town life -- United States -- Fiction; Thrillers (Fiction); Noir fiction